A Metal–Polyphenol‐Coordinated Nanomedicine for Synergistic Cascade Cancer Chemotherapy and Chemodynamic Therapy. Issue 6 (13th December 2019) - Ren, Zhigang; Sun, Shichao; Sun, Ranran; Cui, Guangying; Hong, Liangjie; Rao, Benchen; Li, Ang; Yu, Zujiang; Kan, Quancheng; Mao, Zhengwei
Abstract: The clinical application of chemotherapy is impeded by the unsatisfactory efficacy and severe side effects. Chemodynamic therapy (CDT) has emerged as an efficient strategy for cancer treatment utilizing Fenton chemistry to destroy cancer cells by converting endogenous H2 O2 into highly toxic reactive oxygen species. Apart from the chemotherapeutic effect, cisplatin is able to act as an artificial enzyme to produce H2 O2 for CDT through cascade reactions, thus remarkably improving the anti‐tumor outcomes. Herein, an organic theranostic nanomedicine (PTCG NPs) is constructed with high loading capability using epigallocatechin‐3‐gallate (EGCG), phenolic platinum(IV) prodrug (Pt‐OH), and polyphenol modified block copolymer (PEG‐ b ‐PPOH) as the building blocks. The high stability of PTCG NPs during circulation stems from their strong metal–polyphenol coordination interactions, and efficient drug release is realized after cellular internalization. The activated cisplatin elevates the intracellular H2 O2 level through cascade reactions. This is further utilized to produce highly toxic reactive oxygen species catalyzed by an iron‐based Fenton reaction. In vitro and in vivo investigations demonstrate that the combination of chemotherapy and chemodynamic therapy achieves excellent anticancer efficacy. Meanwhile, systemic toxicity faced by platinum‐based drugs is avoided through this nanoformulation. This work provides a promising strategy to develop advanced nanomedicine for cascade cancer therapy. Abstract : An organic theranostic nanomedicine with high loading capability and interesting stimuli‐responsiveness is developed on the basis of metal–polyphenol coordination. The nanomedicine specifically opens the floodgate in cancer cells to release anticancer drugs and reactive oxygen species through cacade reactions, achieving combination chemo/chemodynamic therapy. In vitro and in vivo studies demonstrate its superb anticancer effect, effectively suppressing the tumor growth.